Role of lysosomal enzymes released by alveolar macrophages in the pathogenesis of the acute phase of hypersensitivity pneumonitis - J. L. Pérez-Arellano; M. N. Barrios; T. Martín; M. L. Sánchez; J. M. González Buitrago; A. Jiménez (Hindawi Limited, 1995)
Hydrolytic enzymes are the major constituents of alveolar macrophages (AM) and have been shown to be involved in many aspects of the inflammatory pulmonary response. The aim of this study was to evaluate the role of lysosomal enzymes in the acute phase of hypersensitivity pneumonitis (HPs). An experimental study on AM lysosomal enzymes of an HP-guinea-pig model was performed. The results obtained both in vivo and in vitro suggest that intracellular enzymatic activity decrease is, at least partly, due to release of lysosomal enzymes into the medium. A positive but slight correlation was found between extracellular lysosomal activity and four parameters of lung lesion (lung index, bronchoalveolar fluid total (BALF) protein concentration, BALF LDH and BALF alkaline phosphatase activities). All the above findings suggest that the AM release of lysosomal enzymes during HP is a factor involved, although possibly not the only one, in the pulmonary lesions appearing in this disease.